Class III/IV POU transcription factors expressed in small cell lung cancer cells are involved in proneural/neuroendocrine differentiation. (September 2014) - Ishii, Jun; Sato, Hanako; Yazawa, Takuya; Shishido‐Hara, Yukiko; Hiramatsu, Chie; Nakatani, Yukio; Kamma, Hiroshi
<x xml:space="preserve">Abstract</x> One‐third of lung malignancies demonstrate a proneural/neuroendocrine phenotype or type of differentiation. However, it has not been clearly elucidated how proneural/neuroendocrine differentiation is controlled in lung cancers. We recently demonstrated that the POU3F2 gene plays a significant role in proneural/neuroendocrine differentiation of lung cancers. Because class III POU genes (POU3F1, POU3F2, POU3F3, and POU3F4) and class IV POU genes (POU4F1, POU4F2, and POU4F3) share similar properties in neural development, we analyzed the association between class III/IV POU genes and a proneural/neuroendocrine phenotype in lung cancers using seven small cell lung cancer (SCLC) cell lines and twelve non‐SCLC (NSCLC) cell lines. Class III/IV POU gene expression was generally restricted to SCLC cells. However, the forced expression of class III/IV POU genes in the NSCLC cell lines induced the expression of neuroendocrine‐specific markers (neural call adhesion molecule 1, synaptophysin, and chromogranin A) and proneural transcription factors (achaete‐scute homolog‐like 1, NeuroD1, and thyroid transcription factor 1) in various degrees. Furthermore, each class III/IV POU gene induced other class III/IV POU genes, suggesting the mutual induction of class III/IV POU genes. These findings suggest that the expression of class III/IV POU genes is important for the proneural/neuroendocrine differentiation of lung cancer cells.